PENERAPAN PENDEKATAN BELAJAR TUNTAS (MASTERY LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Harahap, Nurmawati (Jurnal Pendidikan Guru, 2018)
This study aims to determine the Application of the Comprehensive Learning Approach (Mastery Learning) To Improve Student Learning Outcomes Mathematics Grade V SDN 123 Pekanbaru. The subjects of this study are students SDN 123 Pekanbaru. The number of students is 31 students consisting of 17 male students and 14 female students. The technique used is the instrument of research conducted with observations made by an observer, tests of limited essays, and field notes. This study was conducted by applying the Mastery Learning approach that has been done for three cycles, it can be concluded that the learning by applying the Mastery Learning approach has a positive impact in improving students learning outcomes in the mathematics lesson with the average value of cycle I which is equal to 70.97 and the percentage of mastery of 45.16%. Then after going to cycle II the average value of student learning approach (mastery learning) again increased by 77.42 with a percentage of completeness of 61.29%. However, the increase in cycle II is still not reached the target set previously then dilajutkan in cycle III. In the third cycle, the average value of students learning approach (mastery learning) again increased by 87.42 with the percentage of completeness of 93.55%. The conclusion that the application of the Completed Learning Approach (Mastery Learning) can improve Improve Student Learning Results of VII Students of SDN 123 Pekanbaru.